Buddhist-like opposite diminishing and non-judging during ketamine infusion are associated with antidepressant response: an open-label personalized-dosing study - Stocker, Kurt; Hartmann, Matthias; Reissmann, Steffen; Kist, Andreas; Liechti, Matthias E. (Frontiers in Pharmacology, 2022)
Background: Cognition that is not dominated by thinking in terms of opposites (opposite diminishing) or by making judgments (non-judging) can be found both in Buddhist/mindfulness contexts and in mental states that are fostered by dissociative psychedelics (N-methyl-D-aspartate antagonists) such as ketamine. Especially for the Buddhist/mindfulness case, both opposite diminishing and non-judging have been proposed to relate to mental well-being. Whether ketamine-occasioned opposite diminishing and/or non-judging relate to increased mental well-being in the form of antidepressant response is unknown, and was investigated in the present study. Methods: In this open-label outpatient study, the dose level and frequency for the ketamine infusions were adjusted individually in close consultation with the patients suffering from depression with the overall goal to maximize antidepressant benefits – a novel dose regimen that we term personalized antidepressant dosing. In general, treatment started with an initial series of ketamine infusions with a dosage of 0.5 mg/kg body weight and was then adjusted (usually increased). A possible relationship between ketamine-induced antidepressant benefits and retrospectively reported peri-infusion experiences of opposite diminishing and non-judging was assessed based on a total of 45 ketamine-infusion treatment sessions from 11 different patients suffering from depression. Opposite diminishing and non-judging were measured with the two items from the Altered States of Consciousness Inventory (ASCI) that measure these concepts. Depression was measured with the Beck Depression Inventory (BDI-II). Results Peri-infusion experiences of both opposite diminishing and non-judging were associated with antidepressant response confirming our hypothesis. Furthermore, opposite diminishing and non-judging were closely related to one another while relating to antidepressant response in distinguishable ways. Conclusion: Future controlled randomized trials with dissociative and other psychedelics and with a larger number of participants are needed to establish the possible link of psychedelically induced opposite diminishing and non-judging with antidepressant response more firmly.